Product Competitiveness based on Consumer Perception: A Case Study of the Tahu Bakso Miwiti MSME in Bogor Raya - Syaniah, Alifia Wardahesa; Alviani, Safira Arafiah; Siregar, Rezani; Fauziah, Siti; Zidane, Tifani Yazid; Sitepu, Rasidin Karo Karo (Indonesian Journal Publisher, 2025)
This study aims to analyze the competitiveness of the Tahu Bakso Miwiti product owned by PT. Nasa Boga Bogor based on consumer perceptions in the Bogor Raya area. The product competitiveness is evaluated through five main dimensions: quality, price, service, innovation, and distribution. The research employs a quantitative descriptive method with data collected via online questionnaires completed by 101 consumer respondents. The results indicate that the majority of consumers have a positive perception of the product’s quality, affordable and competitive pricing, fast service, and product flexibility that meets consumer needs. Tahu Bakso Miwiti holds a strong position in the local market with higher consumer preference compared to main competitors. These findings provide a foundation for developing adaptive marketing strategies oriented towards consumer needs to enhance product competitiveness in the local processed food market.